Rapid detection and quantification of apolipoprotein L1 genetic variants and total levels in plasma by ultra‐performance liquid chromatography/tandem mass spectrometry. (20th October 2013) - Zhou, Haihong; Hoek, Maarten; Yi, Pan; Rohm, Rory J.; Mahsut, Ablatt; Brown, Patricia; Saunders, Jason; Chmielowski, Rebecca A.; Ren, Ning; Shuster, Dan; Southwick, Katie; Ayanoglu, Gulesi; et al.
Abstract : RATIONALE: Human genetics studies in African Americans have shown a strong correlation between polymorphisms in the ApoL1 gene and chronic kidney disease (CKD). To gain further insight into the etiology of ApoL1‐associated kidney diseases, the determination of circulating levels of both wild type as well as ApoL1 variants could be of significant use. To date, antibodies that discriminate between all three ApoL1variant forms (wild type, G1 and G2) are not available. We aimed to develop a rapid method for detecting and quantifying ApoL1 variants and total levels in plasma. METHODS: Ultra‐performance liquid chromatography (UPLC) and tandem mass spectrometry (MS/MS) in multiple‐reaction monitoring acquisition mode was used to quantify ApoL1. RESULTS: We demonstrated that it is feasible to detect and quantify ApoL1 variants (wild type, G1 and G2), and total ApoL1 concentrations in plasma. ApoL1 genotypes determined by LC/MS agreed perfectly with the traditional method DNA sequencing for 74 human subjects. The method exhibited at least three orders of linearity with a lower limit of quantification of 10 nM. Moreover, the method can readily be multiplexed for the quantification of a panel of protein markers in a single sample. CONCLUSIONS: The method reported herein obviates the need to perform DNA genotyping of ApoL1 variants, which is of significant value in cases where stored samples are unsuitable for DNA analysis. More importantly, the method could potentially be of use in the early identification of individuals at risk of developing CKD, and for the stratification of patients for treatment with future ApoL1‐modifying therapies. Copyright © 2013 John Wiley & Sons, Ltd.